FROM PRIOR KNOWLEDGE ABOUT HUMAN DEVELOPMENT TO STUDENTS’ UNDERSTANDING ABOUT CHILDREN'S DEVELOPMENT IN SCHOOL - Liah Rosdiani Nasution (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2023)
This research explores the relationship between prior knowledge of human development and students' understanding of teacher candidates regarding child development issues in schools. 366 student teacher candidates from various teaching programs at UIN Syekh Ali Hasan Ahmad Addary became participants in this study. Data regarding prior knowledge of human development and understanding of child development issues in schools were collected through a scale-based questionnaire which was then analyzed through Pearson Product Moment analysis. The results of the analysis show that the relationship between the variable prior knowledge about the stages of human development and the variable understanding of child development issues at school is strong and significant (significance level = 0.99, p value <0.05). From these results, it can be concluded that student teacher candidates who have better knowledge about the stages of child development tend to have a better understanding of the developmental issues faced by children in the school environment.